The remarks on the polygenesis of mountains relief (exemplified by the Carpathians): https://doi.org/10.26485/AGL/2017/106/3 - Starkel, Leszek (Acta Geographica Lodziensia, 2018)
The relief of the Carpathians has the features of a polygenic and polychronic landscape. On polygenesis, we may talk in a double context. The young forms are developing at the present time by cooperation of various processes (mainly erosion of flowing water, piping and gravitational movements). The fundamental forms of the existing mountain relief were created usually in the distant past under varying tectonic and climatic conditions. The inherited relief has been preserved depending on the resistance of bedrock being permanently adapted to changing conditions. Particularly distinct markers of that adaptation in the Carpathians were left by the last glacial-interglacial cycle.